Aplicação de métodos teóricos na investigação da transferência auto-consistente de elétrons em nano-retificador orgânico - ALEIXO, Vicente Ferrer Pureza (Universidade Federal do Pará, 2013)
In this work we present a theoretical study on the electronic structure of a molecule of the type Donor- dinitrobenzene and a group Acceptor- dihydrophenazine (D-A) with polienic bridges varying of π = 0 to the π = 10. It’s a promising system for construct molecular rectifiers that under chemical to dope can come to acquire electric properties of conductive material. It is still, under action of external electric field it presents equivalent behavior to the of usual devices, with countless advantages, for instance, extremely reduced size and intense optical response in a non-linear regime. To study this class of system, we optimize the geometry systematically, performing ZINDO/S-CI (Zerner´s Intermediate Neglect of Differential Orbital/Spectroscopic – Configuration Interaction Single) calculations and using 220 configurations as average. We observe the electronic transfer calculated by Hartree-Fock. Our results show a well defined localization of the Boundary Molecular Orbitals (BMOs) HOMO [LUMO] at the D [A] groups for large polienic bridges. The opposite is verified for small bridges and uniformity is observed for the BMOs in the DA terminals. This would indicate that only large polienic bridges work for devices using the LUMO as conduction channel. A detailed analysis of the molecular charge rearrangement due to an external electric field shows that the charge transport at the D [A] group is bridge size independent. An applied voltage suffices to create a saturation potential for this system with too close DA groups (presenting a saturation and an operation region to systems with small bridges), usually present in systems with relatively large molecular bridge and in macroscopic semiconductors devices. We believe that the LUMO play an important role in the charge transfer at relatively large structures, in addition to fails in molecular structures where the D group is too closer to A. Our results show that we have a Molecular rectifier that works as a macroscopic rectifier.